Pembangunan Sistem Manajemen Finance Accounting dan Human Resource Development pada Perusahaan Jasa Konstruksi (Studi Kasus: AMF-HAQ) - Robi Rizal Anas; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
AMF-HAQ is a construction service company that was founded in 2006 in the West Jakarta area. In carrying out its business activities, the accounting and human resources divisions have several problems which of course can hinder AMF-HAQ's development. In the accounting division, the recording of financial statements is still recorded using Excel which causes file accumulation. Therefore, eventually some problems arise, such as the absence of data backup if data is damaged or lost, the data search process takes a long time, and it takes a long time to make financial reports in graphical form. For the human resources division, important employee data is still stored in Excel and there is no data integration with the project management division. This can cause problems such as no data backup if data is damaged or lost, the data search process takes a long time, and makes the project management division work less efficient. For this reason, the owner of the AMF-HAQ company needs a system that can be used to assist the process of recording financial and employee data. Therefore, a finance accounting and human resource development management system was created. This system will be used by the finance accounting and human resource development divisions to record financial and employee data at the AMF-HAQ company. This system provides features for recording transaction data, both income and expenses, employee data, journal reports, general ledger reports, and balance reports. This system is built using the ReactJS framework for front end, using GraphQL for back end and using MongoDB for saving data via cloud. For system testing, white box method will be used in unit testing and black box method will be used in validation testing.. In addition, for testing system's non-funcional requirement, compatibility testing will be used to testing the system can run or not in different web browser. Testing result shows 100% of the system requirements have been used and valid.